The Role of Consumer Satisfaction in The Influence of Store Atmosphere, Service Quality, And Digital Marketing on Consumer Loyalty at The Legend Bar and Restaurant Legian, Kuta, Bali - Debel, Gede Bagus Ivan Suartika; Junaedi, I Wayan Ruspendi; Adinegara, Gusti Ngurah Joko; Trimurti, Christimulia Purnama (Eastasouth Institute, 2025)
This study aims to analyze the influence of store atmosphere, service quality, and digital marketing on consumer loyalty, with consumer satisfaction as a mediating variable at The Legend Bar and Restaurant, Legian, Kuta, Bali. This research employs a quantitative approach using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The sample consists of 110 respondents who are restaurant customers. The findings indicate that store atmosphere, service quality, and digital marketing positively and significantly affect consumer satisfaction. Furthermore, consumer satisfaction directly influences consumer loyalty. Mediation analysis reveals that consumer satisfaction partially mediates the relationship between store atmosphere, service quality, and digital marketing on consumer loyalty. The implications of this research highlight the importance of optimizing an attractive store atmosphere, improving service quality, and implementing effective digital marketing strategies to enhance customer loyalty in the restaurant industry.